Production frontier analyses: comments on the methodology - Grytten J (Blackwell Synergy, 2000)
Two papers on production frontier analyses have been published in this journal (1, 2). These analytical techniques have been widely used within health economics during the last 20 years. The focus of the analyses has been to identify the most efficient physician practices and hospitals. Although these techniques are promising, they have their shortcomings (for a discussion see references 3, 4). In particular, careful thought must be given to the policy implications that can be drawn from the results.